2023
DOI: 10.3390/s23239361
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost EEG Multi-Subject Recording Platform for the Assessment of Students’ Attention and the Estimation of Academic Performance in Secondary School

Victor Juan Fuentes-Martinez,
Samuel Romero,
Miguel Angel Lopez-Gordo
et al.

Abstract: The level of student attention in class greatly affects their academic performance. Teachers typically rely on visual inspection to react to students’ attention in time, but this subjective method leads to inconsistencies across classes. Online education exacerbates the issue as students can turn off cameras and microphones to keep their own privacy. To address this, we present a novel, low-cost EEG-based platform for assessing students’ attention and estimating their academic performance. In a study involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Different authors support the need to assess the skills that teachers demonstrate when interacting with digital tools. While some authors propose models for assessing teachers during class situations [ 34 , 35 , 36 , 37 , 38 , 39 ], a different set of authors opt to use digital competency assessment frameworks [ 17 , 41 , 42 , 43 , 44 , 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors support the need to assess the skills that teachers demonstrate when interacting with digital tools. While some authors propose models for assessing teachers during class situations [ 34 , 35 , 36 , 37 , 38 , 39 ], a different set of authors opt to use digital competency assessment frameworks [ 17 , 41 , 42 , 43 , 44 , 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 36 ] present a similar proposal based on the use of an Extended-Efficient Layer Aggregation Network (E-ELAN) applied in Smart Classroom environments. On the other hand, Fuentes-Martinez et al [ 37 ] propose an alternative solution to using cameras and microphones to record the classroom, by using low-cost EEG platforms. Their objective is to analyze beta bands obtained from EEG to determine a student’s attention level and provide feedback to the teacher.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, a randomized controlled trial revealed that a lower frontal α power was significantly associated with a higher incidence of postoperative delirium [ 26 ], which is usually a reversible disturbance in mental status with a degree of inattention [ 27 ]. Another study reported that the results demonstrated a significant correlation between the power spectral density of the EEG β band and students’ academic performance, which relates to their attentional ability [ 28 ].…”
Section: Discussionmentioning
confidence: 99%